1985
DOI: 10.3181/00379727-179-42066
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes of the Sweet Protein Monellin as Measured by Fluorescence Emission

Abstract: Monellin is a protein that tastes sweet. In the native state it is a dimer composed of two dissimilar noncovalently associated polypeptides. The conformation of the protein is a determinant of its sweetness, and the present investigation takes advantage of the fluorescence spectrum being a sensitive index of its conformation. The emission spectrum is used to evaluate the ability of temperature and pH to alter the conformation and the sweetness of the protein.When monellin dissolved in water is heated in discre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…1 Lower for an excitation wavelength of 295 nm. The fluorescence of the protein solution has its maximum at 342 nm, in agreement with previous reports (19,20). The fluorescence spectrum is practically unaltered for excitation wavelengths between 290 and 300 nm.…”
Section: Resultssupporting
confidence: 91%
“…1 Lower for an excitation wavelength of 295 nm. The fluorescence of the protein solution has its maximum at 342 nm, in agreement with previous reports (19,20). The fluorescence spectrum is practically unaltered for excitation wavelengths between 290 and 300 nm.…”
Section: Resultssupporting
confidence: 91%
“…X‐ray and NMR methods have resolved the structure of monellin with four anti‐parallel β‐sheets and one α‐helix [26,27]. The protein is very stable against acidification of solution, but undergoes heat and chemical denaturation rather easily [28–34]. The denaturation processes are often irreversible [28,29], and the tendency suggests that the system may be useful for studying protein aggregation phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Its two chains, A and B, are held together by interchain hydrophobic interactions, H-bonds, and salt bridges, [47][48][49] and its biological activity (sweetness) is dependent on the integrity of its secondary, tertiary, and quaternary structure. [50][51][52][53][54][55] A sweet single-chain variant of monellin (MNEI or scMN) has been created through genetic fusion, by joining the C-terminal end of chain B to the N-terminal end of chain A with a Gly-Phe linker. Single-chain monellin has been used extensively as a model protein for folding studies.…”
mentioning
confidence: 99%
“…Naturally occurring monellin (dcMN), isolated originally from the berry of an African plant, Dioscoreophyllum cuminisii , is heterodimeric. Its two chains, A and B, are held together by interchain hydrophobic interactions, H-bonds, and salt bridges, and its biological activity (sweetness) is dependent on the integrity of its secondary, tertiary, and quaternary structure. A sweet single-chain variant of monellin (MNEI or scMN) has been created through genetic fusion, by joining the C-terminal end of chain B to the N-terminal end of chain A with a Gly-Phe linker. Single-chain monellin has been used extensively as a model protein for folding studies. , There have been relatively few studies of the folding of dcMN, , partly because of the heterogeneity observed in the commercially available protein, , but the recent availability of a good bacterial expression system has made dcMN an attractive model protein for the study of the folding of a heterodimeric protein.…”
mentioning
confidence: 99%